Studying the effective dose of polyphenols extracted from green tea in ameliorating the deleterious effect of iron overload in female rats: Khalisa K. Khudiar1 and Nabeel M. Naji2 - Khudiar, Khalisa K. (The Iraqi Journal of Veterinary Medicine, 2012)
experiment aimed at studying the effective dose of total polyphenol extracted from green tea in ameliorating the deleterious effect of iron overload in rats, where forty eight adult female rats were randomly divided into eight equal groups (each of six) and injected intraperitoneally (i.p.) with iron dextran (100mg/kg B.W each 72 hour and treated orally for one month successive increasing dose of GTPs daily (75, 100, 125, 150, 175, 200, and 225 mg/kg B.W.). Measurement of serum iron, albumin, reduced glutathione, peroxynitrate concentration and catalase activity was used as a guide for the detection of the effective dose of total polyphenol that ameliorating the deleterious effect of iron overload. According to this study, the maximum effective dose of total poly phenol extracted from green tea that ameliorating the deleterious effect of iron overload in female rats were found to be equal to 200mg/kg B.W.due to results showed that maximal reduction in serum Iron concentration in groups (T5, T6 and T7) which received total polyphenol orally (175, 200 and 225) mg/kg respectively with mean value equal to (345.87±12.48, 331.73±4.09and 327.27±4.99) respectively as compared with control group (308.68±12.03) after 30 days of treatment, also the best and successive increments in antioxidant enzyme and reduction in free radical status shown in doses of (200 and 225) mg/kg polyphenol, and no significant statistic differences between this groups in all above parameter.